BIOWASH AZAMA: INNOVATIVE ORGANIC WASTE REDUCING PRODUCT TO SUPPORT SCIENCE LEARNING IN CLASS V PRIMARY SCHOOL - Anis Fidiyaningrum; Wita Ermayanti; Joko Sulianto (Schola, 2024)
Waste is one of the big problems in Indonesia which must immediately receive special attention in its handling. If it is not organized properly it will cause negative impacts such as environmental pollution which can damage the ecosystem. The increasing number of Indonesian people causes waste generation to also increase. So efforts are needed to process waste through prevention, reduction, recycling and reuse. The largest waste generation was recorded as 80% originating from organic waste (Oktavia & Rosariawari, 2020). Based on this background, the objectives of the Biowash Azama activity are: 1) increase students' understanding of processing waste, especially organic waste; 2) explain the process of making Biowash Azama so that it can speed up the process of decomposing organic waste; 3) invite students to practice directly processing organic waste; 4) invite students to be role models for the surrounding environment. The method the author uses is a qualitative descriptive method which is useful for exploring the perceptions and understanding of students and teachers regarding the Biowash Azama product as a science learning medium. In this method, interviews or observations can be conducted to collect data about how students receive learning with this product, as well as the impact they feel in terms of understanding environmental concepts and the decomposition of organic waste. The results achieved from this activity are that students better understand the concept of decomposing organic waste and the importance of environmentally friendly waste management, students know the steps for processing organic waste in a short time, students can practice directly processing organic waste, and students can become role models in their families each.